Critical Review on Factors Determining High Performance Organizations within Small-Scale Plastic Components Manufacturing Industry in India - Jayaraj, Balaji; Isaac, Osama; Bhaumik, Amiya (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, organisations seem to be focus mainly on achieving a sustainable growth and also a long-term success through delivery high quality products and services. It is important for the organizations to achieve organizational excellence and competence in the industry in order to survive in the highly competitive business environment. This paper focuses on conducting an extensive literature review on identifying and addressing the factors associated with the high-performance organizations (HPO) in the small-scale plastic components manufacturing industry in India. An HPO model has been provided at the end of the literature review addressing the linkages between the dependent and independent variables.